The Relationship Between Maternal Malnutrition And The Risk Of Premature Birth - Wa Ode Nadziyran Urufia (Oshada, 2024)
Preterm birth is a serious global health problem, given the high morbidity and mortality rates in infants born before 37 weeks gestation. Preterm infants are at high risk of various health complications, including respiratory distress and developmental delays. One of the main risk factors affecting preterm birth is maternal malnutrition. Malnutrition during pregnancy can impair fetal development and the function of the placenta, which plays an important role in providing the fetus with the nutrients and oxygen it needs. Deficiencies in essential nutrients, such as protein, iron, calcium and folic acid, increase the risk of preterm birth. In addition, low socioeconomic conditions, limited access to nutritious food, and lack of nutrition knowledge also contribute to malnutrition in pregnant women. This study used a literature review method to examine the relationship between malnutrition in pregnant women and the risk of preterm birth. Reviewing relevant scientific sources, this study aims to deepen the understanding of the impact of malnutrition on pregnancy and provide recommendations for effective nutrition interventions to reduce the risk of preterm birth and improve maternal and infant health.